The feasibility of implementing a digital pregnancy and postpartum support program in the Midwestern United States and the association with maternal and infant health - Colleen J. Klein; Matthew Dalstrom; William F. Bond; Jeremy McGarvey; Melinda Cooling; Katelyn Zumpf; Lisa Pierce; Brad Stoecker; Jonathan A. Handler (Preventive Medicine Reports)
Objective: The benefits of mobile applications in the prenatal period remain understudied. This study assessed associations between the Pregnancy Postpartum Support Program (PPSP), a digital wraparound service, and maternal and infant outcomes in a Medicaid population. Methods: A retrospective analysis was conducted on pregnant patients with Medicaid insurance who received care and delivered in a Midwestern United States healthcare system between 8/1/2022–8/15/2023, comparing outcomes among those who did versus did not opt for PPSP enrollment. Enrolled patients were offered a mobile device app providing weekly education, “twenty-four seven” support from a clinical team, and telehealth provider visits. Adjusted multiple covariate analyses were completed using linear and logistic regressions. Patient engagement, vendor-based interaction and perception of care data were also examined. Results: 1912 patients were evaluated: 397 in the PPSP and 1515 in the control group. PPSP cohort inclusion was associated with 4 % lower maternal length of stay (LOS) (p = 0.05), 14 % lower infant LOS (p < 0.01), higher mean infant birthweight (p < 0.01), lower odds of birthweight <2500 g (p = 0.05) and lower odds of preterm birth (p = 0.04). Nearly 85 % of all enrolled reported being “very satisfied” with the program. Conclusions: Overall, the program was positively received by PPSP participants. Favorable outcomes associated with enrollment may be due to the program, unmeasured variables, or both. Our study shows the feasibility of offering digital support to pregnant women who voluntarily enrolled in the PPSP and adds to the evidence evaluating virtual care strategies.